2007
DOI: 10.1080/07060660709507457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of foliar fungicide application methods on soybean

Abstract: A field trial was conducted at Fargo, North Dakota, in 2005 and 2006 to evaluate different fungicide application methods on soybean (Glycine max). Kromekote ® paper cards were placed in the upper and lower canopy of soybean plants, and tebuconazole fungicide mixed with a blue dye was sprayed with different application methods at the R5 developmental stage. The applications were made with a conventional sprayer with Turbo TeeJet ® 110015 flatfan nozzles at 276 kPa liquid pressure, a conventional sprayer with X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
1
6
1
1
Order By: Relevance
“…Mean top coverage was 18% at Boone and 17% at Chariton, but ranged from 1% to 8% mean coverage at the bottom or middle canopy positions depending on site and canopy position. Bradley et al (2007) also reported similar results in their work on soybeans, that is, coverage in the upper canopy was considerably greater than coverage in the lower canopy. Deposited droplet size was reduced at lower canopy locations.…”
Section: Depositionsupporting
confidence: 65%
See 3 more Smart Citations
“…Mean top coverage was 18% at Boone and 17% at Chariton, but ranged from 1% to 8% mean coverage at the bottom or middle canopy positions depending on site and canopy position. Bradley et al (2007) also reported similar results in their work on soybeans, that is, coverage in the upper canopy was considerably greater than coverage in the lower canopy. Deposited droplet size was reduced at lower canopy locations.…”
Section: Depositionsupporting
confidence: 65%
“…equivalent across all application treatments and the unsprayed check (table 11). Tebuconazole did not affect soybean yield in similar field trials in North Dakota (Bradley et al, 2007). Although crop yield in this study was unaffected by fungicide application treatment, results may have been different under high disease pressure.…”
Section: Areacontrasting
confidence: 48%
See 2 more Smart Citations
“…Currently the only method of controlling the disease is the application of foliar fungicides (Ozkan et al, 2006). Soybean rust generally initiates in the lower portion of the soybean canopy and moves upward; thus canopy penetration and good coverage from spray applications are critical when applying fungicides to treat soybean rust (Wolf and Daggupati, 2006;Zhu et al, 2006;Bradley et al 2007;Mueller, 2007).…”
Section: Introductionmentioning
confidence: 99%